The Role of Presence /Absence of Palmaris Longus and Fifth Flexor Digitorum Superfiscialis Tendons in Carpal Tunnel Syndrome - A.R Saeid; A Ziaei (Journal of Kerman University of Medical Sciences, 2009)
Background & Aims: Etiologically the causing factor of carpal tunnel syndrome is not clear and multiple contributing factors such as the presence or absence of Palmaris longus tendon have been cited. The aim of the present study was to compare patients with carpal tunnel syndrome and healthy individuals in regard to the absence and presence of Palmaris longus and fifth flexor digitarum superficialis tendons. Methods: This prospective study was performed on 60 diseased and 180 normal hands. Presence or absence of each tendon was determined carefully by the same examiner in both groups. Data were compared by Chisquare test. Results: The relationship between carpal tunnel syndrome and the absence of Palmaris longus tendon and fifth flexor digitorum superficialis was significant (P=0.041 & P=0.05 respectively). Carpal tunnel syndrome group compared to the control group had higher rate of the absence of both tendons in one hand (P=0.017) and lower rate of the presence of both tendons in one hand (P=0.005). By considering only the hands with Palmaris longus tendon, there were more cases of absence of fifth flexor digitorum superficialis in carpal tunnel syndrome group (P=0.048), but by considering only the hands with fifth flexor superficialis, there was no significant difference between the two groups in regard to the presence of Palmaris longus tendone. Conclusion: It seems that the absence of Palmaris longus tendon and fifth superficial flexor each alone and in combination is a risk factor for development of carpal tunnel syndrome. Probably the absence of superficial flexor is a greater risk factor than the absence of Palmaris longus.